1991
DOI: 10.1016/0035-9203(91)90421-t
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic effects of quinine in children with severe and complicated Plasmodium falciparum malaria in Dar es Salaam

Abstract: Quinine is widely used for the treatment of severe and complicated malaria, although resistant strains of Plasmodium falciparum may occur. The drug has been incriminated as a cause of hypoglycaemia in some malaria patients. To determine if quinine has untoward metabolic effects during treatment of severe and complicated malaria we have studied the effects of quinine on blood glucose and intermediary metabolites, serum insulin, C-peptide, plasma glucagon and non-esterified fatty acids in 97 children with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Abdallah et al [ 22 ] observed hypoglycemia in 12% of adult subjects receiving intravenous quinine for severe malaria. However, Kawo et al [ 23 ] did not observe significant changes in blood glucose in subjects with falciparum malaria receiving intravenous administration of quinine.…”
Section: Discussionmentioning
confidence: 99%
“…Abdallah et al [ 22 ] observed hypoglycemia in 12% of adult subjects receiving intravenous quinine for severe malaria. However, Kawo et al [ 23 ] did not observe significant changes in blood glucose in subjects with falciparum malaria receiving intravenous administration of quinine.…”
Section: Discussionmentioning
confidence: 99%
“…In none of our cases, hypoglycaemia could be established . Kawo et al [12], in their study of 97 Tanzanian children found hypoglycaemia in none of the cases on admission and after quinine infusion. The said study was faulted by White' [13], for its design and patient study group (no case of severe falciparum malaria) which were refuted by the author.…”
Section: Discussionmentioning
confidence: 91%
“…Abdallah et al [21] observed hypoglycemia in 12% of adult subjects receiving intravenous quinine for severe malaria. However, Kawo et al [22] did not observe significant changes in blood glucose in subjects with falciparum malaria receiving intravenous administration of quinine.…”
Section: Discussionmentioning
confidence: 92%